Corpogramas: A vestimenta e a dobra como vetores de sentido - Christiana Guady Firmato Brant (2007)
This text is a result of a study carried out between August 2005 and 2007, having as an object of study the unveiling of the use of fabrics and clothing in my practice as an artist. I sought to unravel the theory and practice of the reflections that concern the theme such as the aspects that evolve in my creative process. As unveiling involves the amplification of the eye, I researched and analyzed the artwork by other artists, through which I captured new intrinsic qualities of the subject-matter fabric - so as to widen the limits of its artistic potentiality. The Corpogramas, as I have denominated them, are bodies that denote an apparition, or in the eminence of vanishing; they are attempts of altered or projected bodies, indicating the impermanency of the body, as it is with fabric.